Light-ion production in the interaction of 96 MeV neutrons with silicon - U. Tippawan (2018)
Radiation effects induced by terrestrial cosmic rays in microelectronics, on board aircrafts as well as at sea level, have recently attracted much attention. The most important particle radiation is due to spallation neutrons, created in the atmosphere by cosmic-ray protons. When, e.g., an electronic memory circuit is exposed to neutron radiation, charged particles can be produced in a nuclear reaction. The charge released by ionization can cause a flip of the memory content in a bit, which is called a single-event upset (SEU). This induces no hardware damage to the circuit, but unwanted re-programming of memories, CPUs, etc., can have consequences for the reliability, and ultimately also for the safety of the system. Data on energy and angular distributions of the secondary particles produced by neutrons in silicon nuclei are essential input for analyses and calculation of SEU rate. In this work, double-differential cross sections of inclusive light-ion (p, d, t,3He and α) production in silicon, induced by 96 MeV neutrons, are presented. Energy distributions are measured at eight laboratory angles from 20° to 160° in steps of 20°. Deduced energy-differential and production cross sections are reported as well. Experimental cross sections are compared to theoretical reaction model calculations and existing experimental data in the literature. © 2005 American Institute of Physics.